# Generating function with binomial coefficients

I want to derive formula for generating function $$\sum_{n=0}^{+\infty}{m+n\choose m}z^n$$ because it is very often very useful for me. Unfortunately I'm stuck:

$$f(z)=\sum_{n\ge 0}{m+n\choose n}z^n= \\ \sum_{n\ge 1}{m+n-1\choose n-1}z^n+\sum_{n\ge 0}{m+n-1\choose n}z^n= \\ zf(z)+\sum_{n\ge 0}{m+n-1\choose n}z^n$$

here, I'm afraid that there is a need for something more sophisticated than above trivial identity. Can you help me?

• Isn't it just the binomial series? – EuYu Jul 30 '12 at 21:07
• If I'm not crazy the GF of that is $$\frac{1}{(1-x)^m}$$ or something similar. Try to think about $(1-x)^{-m}$ and how to change $-m\choose n$ to something in terms of positive integers. – Pedro Tamaroff Jul 30 '12 at 21:09
• GF of that is $$\frac{1}{(1-z)^{m+1}}$$ – ray Jul 30 '12 at 21:18
• Yes, precisely. You're trying to prove that? – Pedro Tamaroff Jul 30 '12 at 21:18
• No, I want to derive that, assuming that I don't know that. What typos? I can correct them, but don't see. – ray Jul 30 '12 at 21:20

The function $\left(1 + z\right)^k$ has series expansion $$\left(1 + z\right)^k = \sum_{n\ge0}\binom{k}{n}z^n$$ We also have the binomial coefficient identity $$\binom{n}{k} = (-1)^k\binom{-n + k - 1}{k}$$ which together gives $$\sum_{n\ge 0}\binom{m+n}{n}z^n = \sum_{n\ge 0}\binom{-m-1}{n}(-z)^n = \frac{1}{(1-z)^{m+1}}$$ which is your required generating function.
$$f_m(z).(1-z)=\sum\left(\binom{m+n}{n}-\binom{m+n-1}{n-1}\right)z^n=\sum\binom{(m-1)+n}{n}z^n=f_{m-1}(z)$$
And obviously $f_0(z)=\frac{1}{1-z}$, so $f_m(z)=\frac{1}{(1-z)^{m+1}}$
• very nice too! I also tried this way and introduced $f_m(z)$ notation but I'm ashamed now, I didn't see that $f_0(z)=\frac{1}{1-z}$ so I thought that the solution isn't explicit. – ray Jul 30 '12 at 21:41